On peculiar components of projector optimal strategy in the model of the normed unit load action on three-pillar building construction - Романюк, В.В. (Problems of Tribology, 2014)
There has been supplemented investigating the strictly convex antagonistic game on the subset of the unit hypercube in as the model of the building resources optimal distribution by projecting the three-pillar construction-support. A theorem about the strict inequality in the relationship between ordinary and peculiar values of projector optimal strategy components in the being investigated convex game has been proved. There has been proved the other theorem on peculiar values of projector optimal strategy components in the being investigated game confinement.